Development of a Sensor Network-Based SMPS System: A Smart LED Monitoring Application Based on Wireless Sensor Network - Yoon Sang Kim; Junho Ko (International Journal of Distributed Sensor Networks)
As the specifications of personal, industrial, and medical devices become increasingly sophisticated, the demand for high power devices is also growing rapidly. Because high power supply devices are needed in order to operate high power devices with high specifications, stability and reliability are important factors to consider when it comes to high power supply devices. Therefore, there have been calls for further research on high quality power supply and monitoring system for high power supply. This paper proposes a sensor network-based smart SMPS (switch mode power supply) system. The proposed system makes power supply stable and efficient by providing output current control and sensor network-based monitoring. The functions of the proposed system were verified through both LED control simulation and monitoring simulation. The feasibility of the proposed system was also examined through various experiments and the results were discussed.